Extended employability framework to facilitate information sharing among decision makers - Mat Adam, Asmera (2019)
Unemployment is caused by various reasons that arise from graduates’ reactive attitude or the decision makers’ actions. Decision makers refer to the higher education institutions (HEI), Malaysian Qualifications Agency (MQA), and the industry who are responsible to ensure that what graduates have learnt in the universities is applicable in the labour market. The current problem with decision makers is that they mostly operate and work in silos, whereby employability information is stored in difference portals. It is crucial for decision makers to keep each other up to date. Nevertheless, they face difficulties in sharing information with each other. Thus, the aim of this study was to develop a collaborative framework to facilitate information sharing among decision makers. The objectives were to identify the components in a collaborative framework, to determine the components in the employability domain, and to propose a new collaborative framework that could facilitate information sharing among decision makers. This study used the survey and interview methods and developed a prototype to identify the proposed collaborative framework. The proposed framework was then validated by the decision makers and several experts in knowledge management. In the evaluation process, the Technology Acceptance Model was employed. The evaluation results showed that the proposed framework had a desirable fit with the employability domain. This model also showed that information sharing existed among decision makers. The study has contributed to the body of knowledge a new collaborative framework that can facilitate information sharing across organisations and to the graduates. The findings will have an important implication for decision makers and graduates, whereby they can find the necessary information in a single portal that can provide ample data.